Design of Pendulum Conveyor Chain and its Driving Device - Lu Jianfu; Ding Jiansheng; Lou Jianjun; Lou Yi (Jixie chuandong)
The pendulum conveyor chain and its driving device are the core part of the pendulum conveyor,the reliability and the stability of the driving device directly affect the normal production and the coating quality of the product. The main technical parameters and the design key points of the pendulum conveyor chain and the structural characteristics of the pendulum conveyor chain and the driving device are described. The multipoint automatic lubricating is adopted to avoid increasing the running resistance of the system due to poor lubrication in the course of operation,leading to the drive device capacity becomes insufficient,thus appear chain crawling and influence on the quality of coating.